Deliberating about Bioethics - Gutmann, Amy (The Hastings Center report, 1997)
In some sense, bioethics was built on conflicts. Abortion, physician-assisted suicide, patients’ demand for autonomy all are staple and contentious issues. And the controversies continue to proliferate. What forum best serves such debates? A look at political theories of democracy can help answer that question. The most promising for bioethics debates are theories that ask citizens and officials to justify any demands for collective action by giving reasons that can be accepted by those who are bound by the action. This conception has come to be known as deliberative democracy.